Perceived Effectiveness of Group Teaching Methods for Community Development among Fish Farmers in Edo State, Nigeria - Osabuohien, Julius I.; Okoedo-Okojie, D. U.; Uwana, G. U. (NIU Journal of Climate Justice and Governance; Vol 12 No 1 (2026): NIU Journal of Climate Justice and Governance, Vol. 12 No. 1, June 2026, 2026)
Research and extension in agriculture have a central role of facilitating the transfer of new technologies to farmers and a search through the literature reveal a low level of agricultural productivity among farmers. This study assessed the perceived effectiveness of group teaching methods among fish farmers in Edo State, Nigeria. Specifically, the study examined the socio-economic characteristics of fish farmers; identified the extension group teaching methods available to the respondents; proven technologies and practices disseminated to and adopted by respondents through group teaching methods; determine effectiveness of group teaching method; their perceived factors that mutilate against the effectiveness of group teaching methods application in the study area. A multistage sampling procedure was used in selecting 86 fish farmers for the study, and data collected with the use of questionnaire and analyzed with frequency counts, percentage mean standard deviation, while Pearson Product Moment Correlation was used for hypothesis testing. Results showed that majority (72.09%) and (63.95%) were mates, married and were between 30 and 50 years. Also majority (60.47%) and (56.98%) has secondary education and fish farming experience of between 6 and 10 years. Most (95.35%) confirm demonstration farms offers opportunity for close physical observation and understanding, while the most preferred extension group teaching method was extension speech/talk (m=2.77), and perceived field trip (m=2.77) as most effective extension group teaching method, most serious constraint faced by fish farmer in the effectiveness of group teaching methods was inadequate interest, whereas respondents had highest participation in fertilizer application technology (m=2.55). age (r=-0.55, P<0.05), household size (r=0.13, P<0.05), fish farming experience (r=0.49, P<0.05), number of fish/pond (r=0.71 P<0.05) and income from fish farming (r=0.53, P<0.05) all have significant relationship with perceive effectiveness of group teaching methods. It was recommended that government and stakeholders in fisheries sub-sector should promote effectiveness of group teaching methods through training as this will increase the preference farmers have for group teaching methods. Keywords: Effectiveness, Group Teaching Methods, Fish Farmers, Community Development.